Development of FLOC (Flipbook Competence) as a Means of Teaching Mathematical Counting for Early Childhood Education Teacher Prospective Students - Sugandi, Eko; Kurniawan, Andri (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Technology and education go hand in hand with the needs of Generation Z, who demand ease in learning. Various kinds of information in digital form will be easily accessible with increasingly sophisticated technological developments, especially in learning. The use of digital books in the form of flipbooks, which are used to train creative thinking and can be used as a means of teaching mathematics calculations for prospective Early Childhood Education teacher students, still needs to be found. So, this research aims to develop a digital book product called FLOC (Flipbook Competence) as a teaching aid for prospective Early Childhood Education teacher students to train in collaborative and creative thinking. This research is development research with a method that refers to the development stages of the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research produces a product in the form of a flipbook application based on FLIPHTML5, which can be accessed via computer or Android devices. The results of product trials show that FLOC (Flipbook Competence) can attract and motivate prospective PAUD teacher students to teach the concept of Numbers. The implication is that FLOC (Flipbook Competence) is also considered to have ease of use and good visualization and to attract students' interest in learning.